Pengaruh Pembiayaan Murabahah, Mudharabah, dan Musyarakah Terhadap Profitabilitas dengan Non Performing Financing Sebagai Variabel Moderasi: Studi Kasus Pada Baitul Maal Wat Tamwil (BMT) UGT Nusantara Periode 2015-2021 - Fajar, Tara Malika; Mardiana, Mardiana (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of murabahah, mudharabah, and musyarakah financing on profitability with NPF as a moderating variable. This type of research is quantitative with data collection techniques using documentation and literature study. The location of this research was conducted at BMT UGT Nusantara which is addressed at 8RMQ+52C, Jl. West Sidogiri, RT.03/RW.02, Sidogiri, Kec. Kraton, Pasuruan, East Java 67151. The population in this study is BMT those in Sidogiri, BMT UGT Nusantara and BMT Maslahah. The sampling technique used in this study was purposive sampling technique. The sample that has been determined by the researcher BMT in Sidogiri, namely BMT Maslahah and BMT UGT Nusantara for the 2015-2021 period and BMT in Sidogiri, namely BMT Maslahah and BMT UGT Nusantara for the 2015-2021 period which issued mudharabah financing, musyarakah financing, murabahah financing, Non-Performing Financing for 7 consecutive years. The data used by researchers on mudharabah financing, musyarakah financing, murabahah financing, NPF, and the existing profitability of BMT UGT Nusantara from 2015-2021 with a total of N = 35. With the dependent variable mudharabah financing, musyarakah financing, murabahah financing, independent profitability. And NPF moderation. To answer the problem the researcher uses classical assumptions and multiple linear regression with the SPSS analysis tool. Mudharabah Financing has no effect on Profitability at BMT UGT Nusantara. Musyarakah financing has a positive effect on profitability at BMT UGT Nusantara. Murabaha financing has no effect on profitability BMT Archipelago UGT. NPF does not moderate the effect of Mudharabah financing on Profitability of BMT UGT Nusantara. NPF does not moderate the effect of Musyarakah Financing on Profitability at BMT UGT Nusantara. NPF moderates the effect of Murabahah Financing on Profitability at BMT UGT Nusantara.